Decomposition and combustion studies of phosphine oxide containing aromatic polyethers - Satpathi, Hirak; Pospiech, Doris; Banerje, Susanta; Voit, Brigitte (Polymer Degradation and Stability, 2014)
A comparative study of the decomposition and combustion behavior of systematically varied linear polyether analogs is reported. Properties of aromatic polyethers of bisphenol A/or 4,4′-dihydroxy biphenyl with bis(4-fluorophenyl) derivatives with phosphorus, -CF3 and methoxy -OCH3 constituents were systematically evaluated. All polyethers were synthesized by nucleophilic aromatic polycondensation. The polymers obtained covered a wide range of weight average molar masses (40,000-125,000 g/mol) as determined by size exclusion chromatography with multi-angle light scattering detection. FTIR and NMR spectroscopy revealed formation of the desired polymer structure of the linear polyarylene ethers. All polymers were easily soluble in common organic solvents, thus enabling processing from solution. Film casting from dichloromethane solution yielded transparent, free standing films with high mechanical stability (tensile strengths up to 63 MPa, E-moduli up to 2.5 GPa and elongations at break up to 35%). The thermal decomposition under nitrogen was accessed by thermogravimetry (TGA) and TGA combined with infrared spectroscopy, while the combustion was examined by pyrolysis combustion flow calorimetry (PCFC). The fire behavior was examined for one polymer (P3) by limiting oxygen index that revealed that the phosphine oxide moieties have a measurable influence on flame retardancy compared to the PSU control. © 2014 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Combustion; Decomposition; Mechanical properties; Phosphine oxide; Poly(arylene ether)